Penggunaan Diksi pada Sinopsis Cerpen Mahasiswa Jurusan Bahasa Indonesia FKIP UBT - Muhammad Ilham; Naim Irmayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This study was motivated by the low level of students’ understanding of the proper and correct use of the Indonesian language, particularly in diction selection in writing short story synopses. The study aimed to describe the forms of language errors found in the short story synopses written by fifth-semester students of Class A in the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, Universitas Borneo Tarakan. This research employed a qualitative descriptive method with a content analysis approach and a case study research design. The research data consisted of language errors found in students’ short story synopses, while the data source was the synopsis texts written by the fifth-semester students of Class A. Data validation techniques were carried out through triangulation and informant review, and the data were analyzed using an interactive analysis model that included data reduction, data presentation, and conclusion drawing. The results of the study showed that there were 26 language errors in the students’ short story synopses, consisting of 15 errors in the use of affixes, 9 diction selection errors, and 2 errors in the use of letters. Based on these findings, it can be concluded that errors in the use of affixes were the most dominant type of error found in the students’ short story synopses.